IMPLEMENTATION OF STUDENT LEARNING OUTCOMES IN THEMATIC LEARNING - Laila Diana Rosifah; Muhammad Ali Akbar (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2023)
Scientific progress needs to be realized in order to obtain quality human resources (HR) in Indonesia that can support national development. These efforts can be carried out with good educational management. This research uses LCD media. This research aims to see students' success in thematic learning in class III. This research was carried out in class III of SD Negeri 1 Loloan Barat. The low level of student learning outcomes is due to the lack of interest in the media used by teachers. The data obtained is data from the cognitive or knowledge domain, the affective domain, and the psychomotor domain. Researchers only take it from the cognitive realm, namely knowledge. By implementing efforts to provide media in the form of animated videos about material on the nature of exchange multiplication, as well as with the instruments used, namely student worksheets in each cycle, namely there are 2 cycles, students are able to show that the results of the data provided have increased. Increasing the percentage of student learning outcomes for each cycle, namely in cycle I it was 50% with 8 students who had completed it and in cycle II it was 87% where 14 students had completed it out of a total of 16 students because 2 students were unable to take part in learning activities.